Flash Recycling of Graphite Anodes. Issue 8 (20th December 2022) - Chen, Weiyin; Salvatierra, Rodrigo V.; Li, John Tianci; Kittrell, Carter; Beckham, Jacob L.; Wyss, Kevin M.; La, Nghi; Savas, Paul E.; Ge, Chang; Advincula, Paul A.; Scotland, Phelecia; Eddy, Lucas; et al.
Abstract: The ever‐increasing production of commercial lithium‐ion batteries (LIBs) will result in a staggering accumulation of waste when they reach their end of life. A closed‐loop solution, with effective recycling of spent LIBs, will lessen both the environmental impacts and economic cost of their use. Presently, <5% of spent LIBs are recycled and the regeneration of graphite anodes has, unfortunately, been mostly overlooked despite the considerable cost of battery‐grade graphite. Here, an ultrafast flash recycling method to regenerate the graphite anode is developed and valuable battery metal resources are recovered. Selective Joule heating is applied for only seconds to efficiently decompose the resistive impurities. The generated inorganic salts, including lithium, cobalt, nickel, and manganese, can be easily recollected from the flashed anode waste using diluted acid, specifically 0.1 m HCl. The flash‐recycled anode preserves the graphite structure and is coated with a solid‐electrolyte‐interphase‐derived carbon shell, contributing to high initial specific capacity, superior rate performance, and cycling stability, when compared to anode materials recycled using a high‐temperature‐calcination method. Life‐cycle‐analysis relative to current graphite production and recycling methods indicate that flash recycling can significantly reduce the total energy consumption and greenhouse gas emission while turning anode recycling into an economically advantageous process. Abstract : Spent graphite anodes can be regenerated by an ultrafast flash recycling method. The valuable battery metals can be easily recovered from the flashed anode products by a 0.1 m HCl post‐treatment. The flash‐recycled anode shows recovered electrochemical performance Life‐cycle‐analysis highlights that flash recycling can significantly reduce total energy and greenhouse gas emissions while turning it into an economically advantageous process.